Challenges for energy efficient wide band gap semiconductor power devices. Issue 9 (5th May 2014) - Roccaforte, Fabrizio; Fiorenza, Patrick; Greco, Giuseppe; Nigro, Raffaella Lo; Giannazzo, Filippo; Patti, Alfonso; Saggio, Mario
<x xml:space="preserve">Abstract</x> Wide band gap semiconductors, and in particular silicon carbide (4H‐SiC) and gallium nitride (GaN), are very promising materials for the next generation of power electronics, to guarantee an improved energy efficiency of devices and modules. As a matter of fact, in the last decade intensive academic and industrial research efforts have resulted in the demonstration of both 4H‐SiC MOSFETs and GaN HEMTs exhibiting <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh18002wqp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VB2</alternatives>/Ron performances well beyond the silicon limits. In this paper, some of the present scientific challenges for SiC and GaN power devices technology are reviewed. In particular, the topics selected in this work will be the SiO2/SiC interface passivation processes to improve the channel mobility in 4H‐SiC MOSFETs, the current trends for gate dielectrics in GaN technology and the viable routes to obtain normally‐off HEMTs.